What's in it for labour? Private social standards in the cut flower industries of Kenya and Tanzania - Lone Riisgaard (Danish Institute for International Studies (DIIS), 2007)
Export of cut flowers from East Africa to Europe is an example of how tightened quality regulations and increasing concern with social and environmental issues have created a highly codified industry. For producers participating in value chains driven by large retailers, adopt-ing social and environmental standards is a requirement and specificities are dictated by the buyers. In this paper focus is on private social standards and the opportunities and challenges they pose for labour organizations, especially trade unions. By incorporating the concept of labour agency, global value chain analysis is widened to encompass not just industrial development but also labour development. The analysis reveals how strongly-driven retailer chains offer more room for labour to exert its agency than the traditional auction strand of the value chain. Labour organizations can choose to `ride' the standards, exploiting them to gain influence and advance their own projects. They can also choose to position themselves against the social standards, thereby contesting the legitimacy of private social standards and at the same time delimiting themselves from exploit-ing some of the opportunities offered by these standards. Labour organizations have been able to influence social standard setting and implementation, and to use standards to further labour representation at production sites. However, their ability to seriously challenge the prevailing governance structure of the flower value chain towards more labour representation appears extremely limited. Indeed, it poses a tremendous task to challenge a governance structure that is driven by large powerful retailers employing strategies such as cost-cutting and just-in-time ordering – strategies that put additional pressure on suppliers and promote labour flexibilization and not labour organization.
Keywords: 330; Zierpflanzenbau; Sozialstandards; Gewerkschaftspolitik; Kenia; Tansania